Manpixiao Decoction Halted the Malignant Transformation of Precancerous Lesions of Gastric Cancer: From Network Prediction to In-Vivo Verification - Li, Yuan; Li, Tao; Chen, Jiena; Zheng, Haocheng; Li, Yicong; Chu, Fuhao; Wang, Sici; Li, Ping; Lin, Jie; Su, Zeqi; Ding, Xia (Frontiers in Pharmacology, 2022)
Manpixiao decoction (MPX), a traditional Chinese medicine formula, is mainly used to improve the gastric mucosal pathology and stomach discomfort in patients with gastric precancerous lesions. Precancerous lesion of gastric cancer (PLGC) refers to intestinal metaplasia and/or dysplasia based on gastric mucosal atrophy. Effective prevention and treatment of PLGC is of great significance to reduce the incidence of gastric cancer. Because of the complexity of the etiology and pathogenesis of PLGC, there is no unified and effective treatment plan in western medicine. In recent years, traditional Chinese medicine has shown obvious advantages in the treatment of PLGC and the prevention of its further progression to gastric cancer, relying on its multi-approach and multi-target comprehensive intervention characteristics. This study is designed to examine the protective effect of MPX against PLGC and further to reveal the engaged mechanism via integrating network pharmacology and in vivo experimental evidence. Network pharmacology results demonstrated that inflammation, immune responses, and angiogenesis might be associated with the efficacy of MPX in the treatment of PLGC, in which the PI3K-Akt, cellular senescence, P53 and protein processing in endoplasmic reticulum were involved. There is a synergistic and complementary effect between the different efficacy herbs in the prescription, and laid the foundation for further verification of its multi-path mechanism. We established a rat model of PLGC using a combination of N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), sodium salicylate, irregular fasting, and ranitidine. Our result showed that MPX improved the pathological condition of gastric mucosa in PLGC rats and reduced the incidence of gastric cancer. Next, the analysis of serum inflammatory cytokines showed that MPX reduced the inflammation-related cytokines (such as IL-1α, IL-7, CSF-1, and CSF-3) in the serum. Additionally, MPX also had a regulation effect on the core region of the PLGC rat "protein/protein phosphorylation-signaling pathway" network, it is showed that MPX can inhibit the phosphorylation of PI3K-AKT, and downregulates the EGFR, β-catenin, and N-cadherin protein levels. These results indicate that MPX halted the PLGC progression through inhibiting EGFR-PI3K-AKT related epithelial-mesenchymal transition process.